Going Indie a documentary on the filmmakers of Davao - Tulio, Beatriz A.
Going Indie: a documentary on the filmmakers of Davao is a media ethnographic study on the local film movement of Davao City. Recently, Davao city hosted FDCP?s first Sining Pambansa (National Cinema) festival last June 2012. Also, the Davao Cinematheque, only the second operational cinematheque in the country, was opened to the public. These mark the possibility of a strong Dabawenyo Film Industry. The study is a Media Ethnography (or the Anthropology of Media) which is an area of study within social and cultural anthropology that emphasizes ethnographic studies as a means of understanding producers, audiences, and other cultural and social aspects of mass media. Making use of Machin?s (2002) Ethnographic Research Method, five local filmmakers that best represent the film community of Davao were interviewed. Through this study, we can assess the thriving Dabawenyo Film Movement through the perception of these independent filmmakers. Going Indie : a Documentary on the Filmmakers of Davao makes use of the Video Documentary as its medium of presenting the narratives of these Indie Filmmakers.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts